SISTEM PENILAIAN SUPPLIER MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Nurjanah, Siti; Lelah, Lelah (JTIK (Jurnal Teknik Informatika Kaputama), 2020)
The development of the business world in the future, is directed to companies that compete with each other to be the best of the good to meet the demands of the global market in the future. In a competitive system, companies win various methods, such as increasing customer satisfaction through quality products, on-time delivery and cost efficiency. To support this development, PT Glostar Indonesia (GSI) needs a system that can assess 16 suppliers of footwear raw material suppliers with a computerized system, because the system that runs is still using semi-computerized and time-consuming large costs. This research requires a weighted sum method, the Simple Additive Weighting (SAW) method. The basic concept of the SAW method is to find a weighted sum of the performance ratings for each alternative on all attributes and produce conclusions. This study aims to build a supplier rating system using the SAW (Simple Additive Weighting) method to help buyers get the expected data with precise and accurate results. Implement the SAW method in the supplier grading system at PT Glostar Indonesia. Provide reports on the results of the supplier evaluation process to facilitate the analysis of supplier criteria performed. Reducing the level of error in decision making so that it can provide maximum results for the company.